1996
DOI: 10.1162/jocn.1996.8.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Global Precedence, Spatial Frequency Channels, and the Statistics of Natural Images

Abstract: A great deal of evidence suggests that early in processing, retinal images are filtered by parallel, spatial frequency selective channels. We attempt to incorporate this view of early vision with the principle of global precedence, which holds that Gestalt-like processes sensitive to global image configurations tend to dominate local feature processing in human pattern perception. Global precedence is inferred from the pattern of reaction times observed when visual patterns contain multiple cues at different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
150
2
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(171 citation statements)
references
References 87 publications
16
150
2
3
Order By: Relevance
“…Visual , 1976;Hughes et al, 1996). The present result might be due to the different temporal characteristics of transient and sustained visual channels.…”
Section: Discussionmentioning
confidence: 63%
“…Visual , 1976;Hughes et al, 1996). The present result might be due to the different temporal characteristics of transient and sustained visual channels.…”
Section: Discussionmentioning
confidence: 63%
“…3 The main goal of experiment 2 was to assess whether the strategies used by the autistic children in the facial identity task imply visual processing different from those used by normal controls, despite equivalent performance. This experiment is built on the argument that low-spatial frequency images convey more configural features than local ones, whereas the local features are primarily conveyed by high spatial frequencies (Hughes et al, 1996;Lamb & Yund, 1993;Shulman & Wilson, 1987). When applied to face recognition, fine details of facial features (i.e., local cues) are available when the stimulus contains high spatial frequencies but not when it contains only low facial frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…Spatial frequencies are integrated in a low-tohigh processing order, with low spatial frequencies being processed faster than high spatial frequencies (e.g., Breitmeyer, 1984). These findings have been related to the more general proposal that the global aspects of an image are available before the finer details (e.g., Hughes, Nozawa, & Kitterle, 1996). By extension, it has been established that the configural properties of a face are better represented at a low than at a high spatial frequency level (e.g., Costen, Parker, & Craw, 1994).…”
Section: Introductionmentioning
confidence: 97%
“…A great deal of empirical evidence points toward a fixed integration process that starts with the coarse information (contained in LSFs) and then moves on to the fine information (contained in HSFs), similar to object or form perception in general (e.g. Hughes, Face Perception 18 Fendrich & Reuter-Lorentz, 1990;Hughes, Nozawa & Kitterle, 1996;Kimchi, 1992;Navon, 1977;Sanocki, 1993) . However, some empirical evidence has also indicated processing can be flexible, as processing is sometimes coarse to fine, while others it is fine to coarse.…”
Section: When Are Sfs Selected? the Microgenetic Approachmentioning
confidence: 99%
“…For the anisotropic-integration hypothesis, the integration order is fixed and the majority of empirical data indicates that LSFs are integrated faster than HSFs (Hughes, Fendrich & ReuterLorenz, 1990;Hughes, Nozawa & Kitterle, 1996;LaGasse, 1993;Parker, Lishman & Hughes, 1992Watt, 1987Watt, , 1988, though one study found that HSFs were integrated faster (McSorley & Findlay, 2002). Bachmann (1987) showed two target images (an eye with an eyebrow and a face) mixed up with eight images of different objects.…”
Section: Empirical Evidence Supporting the Hypothesis Of Anisotropic mentioning
confidence: 99%